2018
DOI: 10.1093/jae/ejy016
|View full text |Cite
|
Sign up to set email alerts
|

Regional Integration and Informal Trade in Africa: Evidence from Benin’s Borders

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…21 Little reliable data exist on informal trade volumes, yet a 2011 estimate places the ratio of informal to formal trade for Nigerian imports from Benin stands at about five to one, and at one to one for Nigeria's exports (Bensassi et al 2019).…”
Section: Spatially Adjustedmentioning
confidence: 99%
“…21 Little reliable data exist on informal trade volumes, yet a 2011 estimate places the ratio of informal to formal trade for Nigerian imports from Benin stands at about five to one, and at one to one for Nigeria's exports (Bensassi et al 2019).…”
Section: Spatially Adjustedmentioning
confidence: 99%
“…In many parts of Sub-Saharan Africa, a large share of international trade ows does not go through ocial customs border posts and is not recorded in ocial customs data: it is generally called informal cross-border trade. Such ows cover many products and sectors, and their total value exceeds, in many cases, the value of ocial trade (Lesser and Moisé-Leeman, 2009;World Bank, 2013;Golub, 2015;Bensassi et al, 2018).…”
Section: Informal Tradementioning
confidence: 99%
“…ICBT is an important sector of economic activity in Africa. It has been shown to outstrip formal regional trade for the African countries where data are available (Ackello-Ogutu and Echessah, 1997;Golub and Mbaye, 2009;World Bank, 2011, 2013Bensassi et al, 2017Bensassi et al, , 2018. ICBT in Sub-Saharan Africa also provides muchneeded employment and enables deeper regional integration (Afrika and Ajumbo, 2012;IMF, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While measurement issues around the volume of cross-border trade flows abound (Mitaritonna and Traoré, 2017), concerted efforts to measure them hint at the scale of these informal flows. For example, a recent national survey at 171 unofficial border crossings in Benin found that informal trade made up a very large share of flows with its neighboring countries, with the ratio of informal to formal trade flows at 5.1 to 1 with Nigeria and 2 to 1 with Togo (Bensassi et al, 2018). Similarly, a comprehensive 2006 survey of Uganda's informal cross-border trade flows into the Democratic Republic of Congo and four other neighboring countries found informal export levels that were 86 percent that of official export flows (Lesser and Moisé-Leeman, 2009).…”
Section: Introductionmentioning
confidence: 99%